2002
DOI: 10.1037/0894-4105.16.4.538
|View full text |Cite
|
Sign up to set email alerts
|

Relearning face-name associations in early Alzheimer's disease.

Abstract: Preliminary evidence for the effectiveness of cognitive rehabilitation interventions based on errorless learning principles in early-stage Alzheimer's disease (AD) was provided by Clare et al. (1999, 2000, 2001). The present study extends these findings in a controlled trial. Twelve participants meeting criteria for probable AD, with Mini-Mental State Examination scores of 18 or above, were trained in face-name associations using an errorless learning paradigm. Training produced a significant group improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1
17

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(135 citation statements)
references
References 45 publications
5
112
1
17
Order By: Relevance
“…To date, behavioral strategies have focused almost exclusively on compensatory strategies (e.g., mnemonics) to enhance memory function in mature adults (31)(32)(33)(34), individuals with mild cognitive impairment (35), and those with Alzheimer's disease (36)(37)(38). These studies demonstrated that significant short-term improvements in certain cognitive functions are achievable in both healthy and impaired populations…”
Section: Results Of Etmentioning
confidence: 99%
“…To date, behavioral strategies have focused almost exclusively on compensatory strategies (e.g., mnemonics) to enhance memory function in mature adults (31)(32)(33)(34), individuals with mild cognitive impairment (35), and those with Alzheimer's disease (36)(37)(38). These studies demonstrated that significant short-term improvements in certain cognitive functions are achievable in both healthy and impaired populations…”
Section: Results Of Etmentioning
confidence: 99%
“…This technique employs learning conditions in which patients are prevented from making errors and is based on various techniques (e.g., vanishing cues and spaced retrieval) that have been previously described for MCI studies. In particular, Clare and collaborators used a combination of methods to successfully produce long-lasting memories for a specific set of face-name pairs (Clare et al, 1999(Clare et al, , 2000(Clare et al, , 2001(Clare et al, , 2002(Clare et al, , 2003a. Furthermore, a single case study by Winter and Hunkin (1999) provided descriptive evidence that errorless learning in AD may lead to better re-learning of familiar names compared to learning with errors.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…A different method is applied for the treatment of memory in AD patients during errorless learning because some previous studies have suggested that cognitive rehabilitation approaches may have positive effects on memory functioning during the earlystages of AD (Backman and Dixon, 1992;Backman, 1996;Clare et al, 1999Clare et al, , 2000Clare et al, , 2001Clare et al, , 2002Clare et al, , 2003aClare et al, , 2009). This technique employs learning conditions in which patients are prevented from making errors and is based on various techniques (e.g., vanishing cues and spaced retrieval) that have been previously described for MCI studies.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…15 However, this evidence is still preliminary, and is largely based on small cohort studies with 3 to 12 participants. [16][17][18][19][20] Although the literature regarding cognitive training in AD is limited, studies in people with MCI and healthy older adults do indicate some benefit. However, the effect sizes are modest, with benefits limited to the specific domain on which the training is focused.…”
Section: Cognitive Trainingmentioning
confidence: 99%